2017
DOI: 10.1039/c7ra07172h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of poly(ethylene terephthalate-co-1,4-cyclohexanedimethylene terephtlatate)-block-poly(tetramethylene oxide) copolymers

Abstract: A series of poly(ethylene terephthalate-co-1,4-cyclohexanedimethanol terephthalate)-blockpoly(tetramethylene oxide) (PETG-block-PTMO) copolymers were synthesized by means of a polycondensation process and characterized using 1 H nuclear magnetic resonance (H NMR) and Fourier transform infrared spectroscopy (FTIR), that confirm the successful synthesis of the material. Differential scanning calorimetry (DSC), small -and wide-angle X-ray diffraction (SAXS and WAXS), and thermogravimetric analysis (TGA) were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
51
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 46 publications
5
51
0
3
Order By: Relevance
“…CHEN et al [55] avaliaram pela técnica de TGA a temperatura de decomposição do PETG com diferentes composições químicas e obtiveram valores de temperatura inicial de degradação entre (401,2 e 405,7) ºC, intervalo este que se aproxima ao valor observado no presente estudo. Ainda para efeitos de comparação, PASZKIEWICZ et al [56] avaliaram a degradação térmica do PETG em duas condições de atmosfera no ensaio de TGA, inerte e oxidante (ar sintético), e verificaram que as temperaturas para uma perda de 90% da massa inicial foram, respectivamente, 602,9ºC e 519,8ºC. Neste estudo, para o mesmo valor de redução de massa e utilizando-se ar sintético, a temperatura final de degradação já mencionada foi de 495ºC, indicando que essa atmosfera acelera o processo de decomposição térmica do PETG.…”
Section: Grupo 1: Análises Térmicas E Químicasunclassified
See 1 more Smart Citation
“…CHEN et al [55] avaliaram pela técnica de TGA a temperatura de decomposição do PETG com diferentes composições químicas e obtiveram valores de temperatura inicial de degradação entre (401,2 e 405,7) ºC, intervalo este que se aproxima ao valor observado no presente estudo. Ainda para efeitos de comparação, PASZKIEWICZ et al [56] avaliaram a degradação térmica do PETG em duas condições de atmosfera no ensaio de TGA, inerte e oxidante (ar sintético), e verificaram que as temperaturas para uma perda de 90% da massa inicial foram, respectivamente, 602,9ºC e 519,8ºC. Neste estudo, para o mesmo valor de redução de massa e utilizando-se ar sintético, a temperatura final de degradação já mencionada foi de 495ºC, indicando que essa atmosfera acelera o processo de decomposição térmica do PETG.…”
Section: Grupo 1: Análises Térmicas E Químicasunclassified
“…Neste estudo, para o mesmo valor de redução de massa e utilizando-se ar sintético, a temperatura final de degradação já mencionada foi de 495ºC, indicando que essa atmosfera acelera o processo de decomposição térmica do PETG. Por fim, o segundo estágio de degradação do PETG, mais acentuado que o do PLA, também foi observado de forma semelhante no estudo de PASZKIEWICZ et al [56]. Este efeito pode estar relacionado a um elemento da composição química do material que necessita de maior energia térmica para decompor totalmente a amostra inicial de filamento ou a resíduos da degradação Seguindo a apresentação dos resultados das análises térmicas, na Figura 7 (a) e (b) são representados os termogramas de DSC obtidos para o PLA e o PETG em diferentes condições, isto é, filamentar (inicial), impressa e injetada.…”
Section: Grupo 1: Análises Térmicas E Químicasunclassified
“…21 These changes in mechanical properties causes physical ageing to be considered the most signicant ageing kinetic in PET that limits its service life. 22,23 PETG (T g ¼ 78 C) is synthesised as PET but substituting a fraction of the ethylene glycol with 1,4-cyclohexanedimethanol (CHDM) causes the end-product to be more ductile but T g only increases by $4 C. 24,25 A potential material could be poly(1,4-cyclohexylenedimethylene-co-2,2,4,4tetramethyl-1,3-cyclobutanediol terephthalate) (PCTT, for its structure see Fig. 1) (T g ¼ 110 C) synthesised by replacing the ethylene in PETG with the rigid 2,2,4,4-tetramethyl-1,3cyclobutanediol (TMCD) causing T g to increase signicantly, $35 C. 26 Thus, PCTT could be suitable for high temperature applications in comparison to PET and PETG.…”
Section: Introductionmentioning
confidence: 99%
“…Segmented copolyester ethers, important class of TPEs, play key role in the industrial applications. One can find Hytrel (DuPont, USA) and Anitel (DSM), a family of compounds where the rigid segment is based on PBT and the flexible segment is poly(tetramethylene oxide) (PTMO) (PBT‐ block ‐PTMO), particularly important materials in industrial applications. Our previous studies confirmed that by using two‐step melt polycondensation process, one can obtain PTT‐based copolymers which exhibit good TPEs properties with high thermal stability.…”
Section: Introductionmentioning
confidence: 99%